Behavior of a Free Dual-Spin Gyrostat with Different Ratios of Inertia Moments - Vladimir Aslanov (Advances in Mathematical Physics)
The attitude motion is studied of asymmetric dual-spin gyrostats which may be modeled as free systems of two rigid bodies, one asymmetric and one axisymmetric. Exact analytical solutions of the attitude motion are presented for all possible ratios of inertia moments of these bodies. The dynamics of free gyrostats with zero internal torque is considered. The dimensionless nonlinear equations of the gyrostat are written in Serret-Andoyer canonical variables. The previously known exact solutions are complemented by new several solutions in terms of Jacobi elliptic functions. The results of the study can be useful for the analysis of dual-spin spacecraft dynamics.